Management of Botryosphaeria canker and blight diseases of temperate zone nut crops. (December 2019) - Moral, Juan; Morgan, David; Michailides, Themis J.
Abstract: Species of Botryosphaeriaceae family cause detrimental damage and yield losses in perennial crops. In California, Botryosphaeriaceae species cause three major diseases, the panicle and shoot blight of pistachio; the canker, dieback, and blight of walnut; and, the band canker of almond. The control of Botryosphaeria diseases of pistachio and walnut by applying synthetic fungicides has been an effective management strategy. Conversely, because the unique disease cycle of almond band canker, attacking the almond trunk through the growth cracks, fungicide applications are not recommended for controlling this disease after expression of symptoms. Whatever the disease, integrating the different management practices, such as cultural practices, plant resistance, or biological control, is a necessity. Here, we review the available management strategies that can be used by pest control advisers and farmers of nut crops in order to control these important diseases. Highlights : Chemical control of diseases caused by Botryosphaeriaceae species alone can fail because of different reasons. Botryosphaeriaceae species could be introduced in pathogen-free areas with the nursery stock. Pruning should be conducted during dry weather to reduce risk of inoculum spread on wounds, improving the ventilation in the canopy, and eliminate inoculum sources of the pathogen. Wide variability exists in the resistance response among pistachio and almond cultivars to the pathogens. Information about walnut resistance is more limited, although all Californian cultivars are susceptible. Vigorous rootstocks induce an exacerbation of almond band canker due to increase growth cracks in the scion. Further research is needed on the biological control of diseases caused by Botryosphaeriaceae species. QoI fungicides (azoxystrobin, pyraclostrobin, or trifloxystrobin), or premixtures of QoI fungicides and carboxamides are the most effective in controlling the blight phase of Botryosphaeria diseases of pistachio and walnut. No field fungicide resistance has been detected in any of the Botryosphaeriaceae species causing cankers and blights of nut crops. Control of large hemipteran insect pests of pistachio is essential since they spread inoculum and create wounds on the fruit. Control of walnut scale(s) needed since infested shoots are predisposed to infection.